2022
DOI: 10.7150/thno.76854
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression in tumor immune microenvironment and its optimization from CAR-T cell therapy

Abstract: Chimeric antigen receptor (CAR)-T cell therapy represents a landmark advance in personalized cancer treatment. CAR-T strategy generally engineers T cells from a specific patient with a new antigen-specificity, which has achieved considerable success in hematological malignancies, but scarce benefits in solid tumors. Recent studies have demonstrated that tumor immune microenvironment (TIME) cast a profound impact on the immunotherapeutic response. The immunosuppressive landscape of TIME is a critical obstacle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 198 publications
0
32
0
Order By: Relevance
“…Several studies have endeavored to integrate chemokines and CAR-T cells to fight cancer, with ongoing investigations focused on CXCR2-modified CAR-T cells that have been shown to induce complete tumour regression and immunological memory in aggressive tumors [ 130 ].…”
Section: Roles Of Cytokines In Drug Resistance In Multiple Myelomamentioning
confidence: 99%
“…Several studies have endeavored to integrate chemokines and CAR-T cells to fight cancer, with ongoing investigations focused on CXCR2-modified CAR-T cells that have been shown to induce complete tumour regression and immunological memory in aggressive tumors [ 130 ].…”
Section: Roles Of Cytokines In Drug Resistance In Multiple Myelomamentioning
confidence: 99%
“…In recent years, tumor immunotherapy has become a hot spot in the eld of tumor treatment research and is also considered one of the most promising treatment methods. Immunotherapy has achieved great success in the treatment of many tumors [37]; however, its therapeutic effect in PC is minimal [38]. In this study, we analyzed the correlation between MINDY2 in PC and immunity and found that MINDY2 was signi cantly and positively correlated with in ltration scores of B cells, T cells CD8+, neutrophil, macrophage, and myeloid dendritic cells in PC, and although there was no statistical signi cance between MINDY2 and T cells CD4+, it can be concluded that the expression level of CD4 + T cells was greater in the MINDY2 high expression group than in the low expression group.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells escape being destroyed by the immune system because the immune cells, such as neutrophils, monocytes, macrophages, dendritic cells, natural killer cells, and B and T lymphocytes, are suppressed [138]. Besides, the tumour immune responses are barred from immune checkpoint activations, thereby causing immune evasion [139]. Therefore, the immune evasion is eliminated by suppressing and inhibiting the both mechanisms.…”
Section: Immune Evasion Therapiesmentioning
confidence: 99%